Supporting children with Cerebral Palsy with a caregiver training program in a northern Malaysian Hospital - Abu Bakar, Muhammad Radhi Rahimi; Talib, Siti Salwa; Baharudin, Nur Sakinah; Shamsudin, Norsyaqina; Ismail, Wan Ismahanisa; Mohd Zin, Mohd Fadil (Universiti Teknologi MARA, Kedah, 2024)
The care of children diagnosed with cerebral palsy (CP) has been demonstrated to adversely affect the physical and psychological health of the primary caregivers. This study aims to provide knowledge and training to caregivers/parents with CP children in handling their children and to examine the overall implementation of this program. A half-day training program for the caregivers of children with CP was conducted. Thirty children with CP (aged 2-12 years), and their caregivers were enrolled on this program held at the Tunku Fauziah Hospital, Kangar. This program consists of three slots which are divided into two talk sessions and one practical session. Caregivers were interviewed and required to complete pre-test questions before the talks and practical session. The post-test questionnaire was completed by the caregivers after the talks and practical session. The result showed significant improvement among caregivers of children with CP regarding their knowledge about cerebral palsy and the knowledge of general development in children. In summary, this caregiver training program built expressly for helping children with cerebral palsy (CP) is critical and provides several benefits that may considerably improve the quality of care and the general well-being of both the child and their carer.